Profiling Cancer Patients Based on Their Motives for Seeking Support Online: Presenter(s): Song Duimel, University of Amsterdam, Netherlands. (April 2023) - Linn, Annemiek; Smets, Ellen; Smit, Eline; van Weert, Julia
Abstract : Background: Understanding why patients seek informational and/or emotional support online is fundamental to providing patients with accurate and reliable support that is tailored to their needs, preferences, and personal situation. Earlier studies provided valuable insights into cancer patients' motives for using the internet but did not account for individual differences in motives that patients may hold to search for different types of support online. Based on stress coping theory and uses and gratifications theory, this study aimed to identify profiles of cancer patients differing in their motives for seeking support online, and to compare the profiles in terms of patients' psychological and Background: characteristics, and perception of health care services. Methods: Hierarchical cluster analysis was conducted, using questionnaire data of cancer patients and cancer survivors visiting a large Dutch health website (N = 181). Findings: The results revealed three distinctive profiles, i.e., overall seekers (seeking for both informational and emotional support, n = 83, 46.0%), occasional information seekers (occasionally seeking for informational support, n = 83, 46.0%), and contact exchangers (mainly seeking for emotional support, n = 15, 8.0%). Patients across these profiles were found to differ in their eHealth literacy, with the contact exchangers being more eHealth literate than the overall seekers and occasional information seekers. Discussion: This study can be used to create awareness among health care providers that there are three different types of cancer patients' that differ in their motives for seeking informational and/or emotional support online. Such awareness can help the providers to tailor referrals to accurate and reliable websites or platforms that fit a specific patient. Based on the results of this study we suggest extending the stress coping theory by acknowledging the interplay of different coping strategies and different gratifications when studying motives for online support seeking.